Accounting Treatment of Lease Obligations and Financial Performance Indicators (gjstudies, 2026)
This research investigates the complex interplay between the accounting treatmentof lease obligations and the subsequent impact on key financial performance indicators,proposing a novel analytical framework that diverges from traditional capital structureanalysis. While existing literature predominantly focuses on the binary classificationof leases as either operating or finance leases under standards such as IAS 17 and itssuccessor IFRS 16, this study introduces a multi-dimensional continuum model. Thismodel assesses lease obligations not merely by their on- or off-balance-sheet status,but by their embedded optionality, duration, and sector-specific economic substance.The methodology synthesizes principles from financial accounting, corporate finance,and contract theory to construct a granular dataset of firm-level lease disclosures fromthe pre-IFRS 16 adoption period (2000-2005). Through a series of multivariate regressions and path analyses, we demonstrate that the mechanical capitalization of allleases, as mandated by newer standards, obscures significant variance in how differentlease portfolios influence metrics such as return on assets (ROA), debt-to-equity ratios, and interest coverage. Our findings reveal that for capital-intensive industries liketransportation and retail, the traditional operating lease treatment created a systematic understatement of leverage that was partially mitigated by market participantsthrough adjustments to credit ratings and cost of capital. Conversely, for technology and service firms, the impact was more nuanced, with lease obligations showinga weaker correlation with perceived financial risk. The study concludes that a onesize-fits-all lease accounting model may fail to capture the economic diversity of leasecontracts, suggesting that supplementary, contract-level disclosure remains critical foraccurate performance assessment. This research contributes originality by reframinglease accounting not as a compliance issue, but as a determinant of fundamental financial signal quality, with implications for valuation models, credit risk assessment, andcorporate financial strategy